Child regulative temperament as a mediator of parenting in the development of depressive symptoms: a longitudinal study from early childhood to preadolescence - Schmidt, Martin H.; Hohm, Erika; Banaschewski, Tobias; Laucht, Manfred (Journal of neural transmission, 2017)
Child temperament as well as parenting behaviors have been linked to adolescent depression. Beyond their main effects, the interplay between these factors is of interest. For example, in an interactive model, a differential susceptibility of temperamental variants to parenting has been suggested. However, so far, the differential susceptibility hypothesis has mostly been studied with a focus on externalizing disorders. On the other hand, parenting may shape the child’s temperament and vice versa in a transactional process. In a prospective, longitudinal at-risk sample (163 boys, 176 girls), we assessed emotional (easy-difficult) and regulative (self-control) temperament at ages 4.5, and 8 years, respectively, as well as parenting quality at age 4.5 years using the HOME inventory. Hierarchical linear regression analysis was used to investigate the prediction of depressive symptoms at age 11, measured by the Child Depression Inventory, including interaction terms between the temperament variable and parenting. We additionally tested whether parenting was mediated by child temperament. As previously reported, both self-control and parenting were longitudinally associated with preadolescent depressive symptoms. There were no interactive effects between temperament and parenting. However, the effects of parenting were partly mediated by self-control. Our data do not support a differential susceptibility of temperamental variants in the development of preadolescent depression. However, our results are in line with the assumption that parenting may shape young children’s temperament, with positive parenting in the early childhood fostering the development of regulative temperament.